Pendidikan Islam Dalam Sistem Pendidikan Nasional Telaah Terhadap UU No. 20 Tahun 2003 - Ristanti, Octiana; Suri, Atika; Choirrudin, Candra; Dinanti, Lutfita Kurnia (Tawazun: Jurnal Pendidikan Islam, 2020)
This article discusses Islamic Education in the National Education system reviewing Law No. 20 of 2003. Article 37 paragraph (2) states that the education curriculum is required to include Religious Education, Citizenship Education, and Language Education. These three compulsory subjects imply that the goal of national education is to try to realize Indonesian people who are religious / religious, a nation that can respect its citizens and national identity with its national language. The multi-dimensional crisis that is being experienced by the Indonesian people can not only be seen and overcome with a mono-dimensional approach. However, because the apangkal of the crisis is the low moral, human morals, religious education has a very large share in building the dignified character and civilization of the nation. For this reason, effective Islamic religious education learning is needed, so that the successful implementation of religious education contributes to the preparation of a generation that has good ethics, morals and good behavior. Conversely, failure in the implementation of religious education will result in the declining morals of future generations and in turn will undermine the character of the nation. This article uses data analysis techniques carried out by manual and digital searches, Islamic education is the process of changing individual behavior in personal life, society, and the natural surroundings, by way of teaching as a human activity and as a profession among the human professions in society. Abstrak Artikel ini membahas tentang Pendidikan Islam dalam sistem Pendidikan Nasional telaah terhadap UU Nomor 20 Tahun 2003. Pasal 37 ayat (2) menyatakan bahwa kurikulum pendidikan wajib memuat Pendidikan Agama, Pendidikan Kewarganegaraan, dan Pendidikan Bahasa. Tiga mata pelajaran wajib ini mengisyaratkan bahwa tujuan pendidikan nasional berusaha untuk mewujudkan manusia Indonesia yang religius/beragama, bangsa yang dapat menghargai warga negaranya dan identitas kebangsaan dengan bahasa nasionalnya. Berbagai krisis multi dimensional yang sedang dialami oleh bangsa Indonesia memang tidak hanya bisa dilihat dan diatasi dengan pendekatan mono dimensional. Namun demikian karen apangkal dari krisis tersebut adalah rendahnya moral, akhlak manusia maka pendidikan agama memiliki andil yang sangat besar dalam membangun watak dan peradaban bangsa yang bermartabat. Untuk itu diperlukan pembelajaran pendidikan agama Islam yang efektif, sehingga keberhasilan penyelenggaraan pendidikan agama berkontribusi terhadap penyiapan generasi yang memiliki etika, moral, dan perilaku yang baik. Sebaliknya, kegagalan dalam penyelenggaraan pendidikan agama akan berakibat terhadap merosotnya akhlak generasi penerus dimasa yang akan datang dan pada gilirannya akan merapuhkan karakter bangsa. Artikel ini menggunakan teknik analisi data dilakukan dengan penelusuran manual dan digital, pendidikan Islam adalah proses mengubah tingkah laku individu pada kehidupan pribadi, masyarakat, dan alam sekitarnya, dengan cara pengajaran sebagai suatu aktivitas asasi dan sebagai profesi diantara profesi-profesi asasi dalam masyarakat.